Tensor spectrum of turbulence-sourced gravitational waves as a constraint on graviton mass. Issue 7 (8th July 2021) - He, Yutong; Brandenburg, Axel; Sinha, Aditya
Abstract: We consider a generic dispersive massive gravity theory and numerically study its resulting modified energy and strain spectra of tensor gravitational waves (GWs) sourced by (i) fully developed turbulence during the electroweak phase transition (EWPT) and (ii) forced hydromagnetic turbulence during the QCD phase transition (QCDPT). The GW spectra are then computed in both spatial and temporal Fourier domains. We find, from the spatial spectra, that the slope modifications are weakly dependent on the eddy size at QCDPT, and, from the temporal spectra, that the modifications are pronounced in the 1–10 range — the sensitivity range of the North American Nanohertz Observatory for Gravitational Waves (NANOGrav) — for a graviton mass in the range 2×10 -23 c 27 ×10 -22 .